Relationship Between Perceived Social Support (Family, Friends and Other Important People) With the Tendency of Using Psychotropic Substances Among the Nurses of Hospitals in Kermanshah City - Peiman Hatamian; Jahangir Karami; Khodamorad Momeni (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Considering the importance of the role of nurses in increasing the individuals' health, family, and society, the present study was conducted to investigate the relationship between perception of social support and tendency of using psychotropic substances in nurses. Methods: The statistical population of this descriptive-correlational study consisted of all nurses of hospitals in Kermanshah (2016). 341 nurses were selected using cluster sampling method and the data-gathering tools was the multi-dimensional scale of social support perception (Zimat et al. 1988) and questionnaire (Bahremand and colleagues, 2014) was applied for the tendency of using psychotropic substances. Data were analyzed by SPSS-22 software, Pearson correlation, and regression analysis tests.  Results: The results of the research showed that there was a significant relationship between the components of the perception of social support and the general score of the tendency toward psychotropic substances. These relationships were meaningful in level (P <0.001). Conclusion: Therefore, it can be concluded that the subscales of the perception of social support can predict the tendency of using psychotropic substances.